Political ecology of geothermal power plants in Turkey : the case of Büyük Menderes and Gediz grabens - Öztürk, Deniz. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2023., 2023)
Over the past twenty years, Turkey has increased its renewable energy investments partly to follow the global driving forces of decarbonization enforced by the international climate change regime, partly to attract finance from international financial institutions, and partly to substitute imported fossil fuel (mainly natural gas) with “domestic and national” energy. The rapid increase in renewable investments, coupled with the increasing authoritarian neoliberalism of the government has taken a heavy toll on the local communities by destroying their livelihoods and violating their political rights, leading to an increasing number of local resistance movements against hydro, wind, and geothermal power plants (GPPs). Against this background, this thesis aims to examine the multidimensionality of the injustices arising from the increased number of GPPs, particularly in Büyük Menderes and Gediz Grabens. A textual analysis of numerous reports, news articles, press releases, and videos was conducted to identify the stakeholders and their proposed alternatives, and to understand environmental justice issues surrounding the conflicts around these GPPs. This analysis was then substantiated by in-depth interviews and participatory observation in the fieldwork in Aydın, Mezeköy. The results of this investigation reveal that GPPs in the region induce massive ecological degradation, deepening the economic inequality by damaging agricultural production and by expropriating livelihoods and living spaces of the local communities, while simultaneously upholding the interests of the business. This inequality is further exacerbated by the increasing authoritarianism of the government, resulting in the deprivation of the cultural, political, and moral rights of the local people.
Keywords: Geothermal power plants -- Turkey.; Grabens (Geology) -- Büyük Menderes.; Grabens (Geology) -- Gediz.